Melampaui Aktualisasi Diri: Kritik Humanistik-Transendental atas Psikologi Abraham Maslow dan Rekonstruksi Teologis Masyarakat Tanpa Kekerasan - Azzumarda Azra; Anisatul Hikmah; Revilatur Rohima Kusi (INDO PUBLISHING, 2026)
The rise of violence in contemporary society—whether in structural, symbolic, or digital forms—indicates a profound crisis in the paradigm of modern humanism, which has not been able to comprehensively address humanitarian problems. Humanistic psychology, pioneered by Abraham Maslow with the concept of self-actualization, offers an optimistic vision of human potential, but still leaves a gap in explaining collective social transformation and the dimension of spiritual transcendence. This research gap lies in the absence of systematic integration between humanistic-existential psychology with Islamic theology and Sufism in formulating a model for a non-violent society. This article uses an interdisciplinary theoretical approach that combines humanistic psychology, transformative theology, and Sufism as an analytical framework. The method used is qualitative-conceptual with a hermeneutic-critical analysis of classical and contemporary literature. The main argument of this study asserts that the concept of self-actualization is inadequate without a shift towards self-transcendence rooted in divine consciousness and inner transformation. Violence is understood as a manifestation of an existential and spiritual crisis that requires human ontological reconstruction. This article's scholarly contribution is to offer a new framework, the